Synthesis and applications of inverse vulcanized polysulfides from bio-crosslinkers - Abdulah, Nayeem; Mohd Faizal, Ali; Jun Haslinda, Shariffuddin (Elsevier Ltd., 2021)
Elemental sulfur, an industrial by-product from petroleum industries worldwide, has drawn sufficient attention to researchers. The limited scope of application has caused a colossal surplus amount of elemental sulfur stacked in the open places. Several polysulfide synthesis processes, including condensation, free-radical process, and ionic copolymerization technique, were used but resulted in unstable products. A new polymerization technique, termed inverse vulcanization, has been introduced, which enabled different types of crosslinkers for polysulfide production and their scopes to explore numerous applications. The current paper concisely reviews the evolution and advances of using vegetable oils and plant extracts in inverse vulcanization to produce polysulfides. The alluring applications and properties have also been discussed briefly.